2008
DOI: 10.1080/00036840600905217
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and R&D: an econometric evidence from Spanish firm-level data

Abstract: This article analyses the relationship between productivity growth and R&D investments of Spanish manufacturing firms during the 1990s. The theoretical model is a version of the Cobb-Douglas production function in its growth rate form. The purpose is to estimate the rate of return to R&D expenditures. The econometric specification is a distributed lag model. The estimation applies the generalized method of moments method. The main empirical finding is that a positive and significant role is played by R&D expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Finally, three metaanalysis studies by Wieser (2005), Moen and Thorsen (2013) and Ugur et al (2014) provide meta-regression evidence on productivity and rates-of-return estimates. 2 The estimated overall rate of return to R&D is positive, generally statistically significant and with a magnitude according to the econometric methodology, data level, the measurement of output and of the inputs, the production function used, whether or not it controls for spillovers effects and the method of measuring spillovers (among others, see Hall and Mairesse, 1995;Harhoff, 1998;Aiello and Pupo, 2004;Maté-García and Rodríguez-Fernández, 2008;Wakelin, 2001;Rogers, 2010). 3 Although family businesses are prevalent in the world, no previous study provides estimates of R&D returns for family firms.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, three metaanalysis studies by Wieser (2005), Moen and Thorsen (2013) and Ugur et al (2014) provide meta-regression evidence on productivity and rates-of-return estimates. 2 The estimated overall rate of return to R&D is positive, generally statistically significant and with a magnitude according to the econometric methodology, data level, the measurement of output and of the inputs, the production function used, whether or not it controls for spillovers effects and the method of measuring spillovers (among others, see Hall and Mairesse, 1995;Harhoff, 1998;Aiello and Pupo, 2004;Maté-García and Rodríguez-Fernández, 2008;Wakelin, 2001;Rogers, 2010). 3 Although family businesses are prevalent in the world, no previous study provides estimates of R&D returns for family firms.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Therefore, a justification for programs intended to stimulate innovative activities rests on the literature that estimates the returns to R&D. Along this line of reasoning, it is not surprising that there is a substantial number of empirical studies assessing the returns to R&D at country, regional, industry and firm-level (for a review of the literature see Hall, Mairesse and Mohnen, 2010; while for meta-analysis studies see Wieser 2005, Moen and Thorsen 2013, and Ugur et al, 2014. Limiting attention to studies at firm level, the evidence reveals a positive relationship between innovation and productivity (among others, see Hall and Mairesse, 1995;Harhoff, 1998;Aiello and Pupo, 2004;Maté-García and Rodríguez-Fernández, 2008;Wakelin, 2001;Rogers, 2010). Unfortunately, this literature has ignored the role of family firms and we have very limited insight about the link between innovation and productivity in family and non-family firms.…”
Section: Introductionmentioning
confidence: 99%
“…Goya et al (2016) and Barge-Gil et al (2019) used the first database, while a higher number of researchers were inclined to use the second one. Among others, one may quote, for example, the papers by Beneito (2001), García et al (2002), Huergo and Jaumandreu (2004), Maté and Rodríguez (2008), Huergo and Moreno (2011), Doraszelsky and Jaumandreu (2013), and Añón-Higón et al (2018.…”
Section: Previous Researchmentioning
confidence: 99%
“…She concluded that these spillover effects were only relevant for those firms that use advanced technologies. On the other hand, the positive effects of innovation on productivity were estimated by Huergo and Jaumandreu (2004) in the case of process innovation; by García et al (2002), who proxied innovation by the knowledge capital of firms; by Maté and Rodríguez (2008), who used the R&D intensity (R&D expenditure divided by the real value added) as an index of technological effort; and, finally, by Doraszelsky and Jaumandreu (2013). Extending the sample of ESEE to more recent years, Huergo and Moreno (2011) and Doraszelsky and Jaumandreu (2018) continued to find evidence of this positive relationship.…”
Section: Previous Researchmentioning
confidence: 99%
“…In the latter case, on which this study focuses, empirical estimates of the rate of return vary between 20% and 50%. Examples include Griliches and Mairesse (1991), Wakelin (2001), Smith, Dilling-Hansen, Eriksson and Madsen (2004) and Maté-Garcia and Rodriguez-Fernandez (2008).…”
Section: Introductionmentioning
confidence: 99%